Kepuasan Kerja Guru dalam Pendidikan Islam: Tinjauan Literatur Sistematis - Setiawan, Okta Iwan; Dermawan, Oki; Maarif, Muhammad Anas (re-JIEM (Research Journal of Islamic Education Management), 2026)
Teacher job satisfaction is a strategic issue in Islamic education because it is related to the quality of learning, organizational stability, and the sustainability of educational services. This study aims to synthesize the determinants, impacts, and directions of conceptual development of teacher job satisfaction in Islamic educational institutions. The method used is a Systematic Literature Review (SLR) based on PRISMA 2020 on articles published in 2019-2025 searched through Google Scholar, Crossref, SINTA/OJS, and Scopus Preview. Of the 126 initial records, 12 primary articles met the inclusion criteria and were analyzed thematically. The results show that teacher job satisfaction in Islamic education is influenced by four groups of factors: material well-being and work facilities, madrasah leadership and culture, professional competence and work motivation, and Islamic spirituality and Islamic work ethics. Job satisfaction impacts increased performance, organizational commitment, loyalty, and reduced work stress, while dissatisfaction is related to the risk of decreased motivation and turnover intentions. This study concludes that teacher job satisfaction in Islamic education cannot be understood solely as a psychological response to compensation, but as a multidimensional construct that combines material, professional, social, and transcendental dimensions. The study’s contribution lies in the formulation of an integrative framework for job satisfaction based on Islamic values â€‹â€‹that can be used as a basis for developing human resource management policies in Islamic schools and educational institutions.